Leiomyoma presenting as an anterior vaginal mass. Issue 3 (2nd March 2023) - Dunphy, Louise; Wood, Francis; Siraj, Mamoon; Neelagandan, Somashekar; Sheldon, Emma; Swaminathan, Ajay
Abstract : Leiomyoma, otherwise known as a fibroid, is commonly encountered in the uterus. Vaginal leiomyomas are extremely rare with a relative paucity of cases reported in the literature. Due to the rarity of the disease and complexity of the vaginal anatomy, definitive diagnosis and treatment are challenging. The diagnosis is often only made postoperatively after resection of the mass. They usually arise from the anterior vaginal wall and women may present with dyspareunia, lower abdominal pain, vaginal bleeding or dysuria. Imaging with a transvaginal ultrasound scan and MRI can confirm the vaginal origin of the mass. Surgical excision is the treatment of choice. The diagnosis is confirmed following histological assessment. The authors present the case of a woman in her late 40s presenting to the gynaecology department with an anterior vaginal mass. Further investigation with a non-contrast MRI was suggestive of a vaginal leiomyoma. She underwent surgical excision. Histopathological features were in keeping with the diagnosis of a hydropic leiomyoma. A high index of clinical suspicion is required to establish the diagnosis as it can be mistaken for a cystocele, Skene duct abscess or Bartholin gland cyst. Although it is a benign entity, local recurrence following incomplete resection and sarcomatous changes have been reported.